Influência do capeamento e caracterização da resistência a compressão de alvenaria estrutural de blocos de concreto - Fortes, Ernesto Silva (2012)
This project aim was to evaluate the compressive strength of masonry concrete block from low to high resistances. This topic is motivated by the observation that there are no reliable parameters for designing the compression strength of masonry concrete block, considering the various options of strength and grouting available, especially for higher strenght blocks (above 12 MPa) whose use has become widespread in Brazil. From the national survey conducted in partnership with the ABCP it was also possible to observe that not always prisms are actually tested as a parameter to control the quality of the job-site execution control in the differents regions of Brazil. Another motivating point of this project is the observation of the difficulty procedure and high dispersion of inter-laboratory test data when testing compression strength of blocks and prisms capped with cement paste. It is also objective to evaluate the possibility of using a dry material, such as plywood, hardboard, and fiberboard for capping, replacing the usual cement paste capping. More than a thousand tests were carried out to determine the axial compression and the modulus of elasticity of grouted and non-grouted prisms and concrete blocks with dry capping and the cement paste and by grinding process for comparative testing. The blocks compressive strength ranged from 5 to 34 MPa. Based on the results it is possible to conclude on the need for proper dosage of the grouting procedure and the executive, which has influence on the prism strength. After a first phase, when all capping materials were considered, the hardboard was chosen as the comparative to cement paste. It is possible to conclude that both capping materials lead to equivalent result when testing concrete blocks. For hollow prism testing, it is not possibly to categorically conclude to the statistically equivalence when considerend all ten resistance ranges tested, but the characteristic value did not result in a difference greater then 10%. In the case of grouted prism we can concludes to the non-equivalence of types of capping. Another important conclusion is the indications of prism (hollow and grouted) / block strength ratio for the several resistances evaluated.